A Unique Case of Asystole Secondary to Facial Injury - Siddharth A. Wartak; Reshma A. Mehendale; Amir Lotfi (Case Reports in Medicine)
Bradycardia has been reported during intraoperative settings of craniofacial, cerebropontine angle and trigeminal ganglion surgeries (Schaller et al. (2009, 1999); Parbhakar et al. (2009); Koerbel et al. (2005); Roberts et al. (1999)). It is also commonly seen in children undergoing orbital and maxillary fractures repair. This mechanism has been described as the trigeminocardiac reflex (TCR) (Schaller et al. (2009, 2004); Kim et al. (2000); Lang et al. (1991); Van Brocklin et al. (1982)). We report an unusual case of posttraumatic bradycardia and recurrent asystole in a previously healthy adult patient from possible TCR in the absence of any surgical intervention to the head and orbital area.